Kuntai Capsule Combined With Letrozole on Gonadal Hormone Levels and Ovarian Function in Patients With PCOS: A Systematic Review and Meta-Analysis - Tang, Xing; Huang, Qinwan; Wang, Chengcheng; Zhang, Da; Dong, Shoujin; Yu, Congcong (Frontiers in Endocrinology, 2021)
Background The efficacy of Kuntai capsule combined with letrozole (LE) in improving ovarian function of polycystic ovary syndrome (PCOS) has been evaluated before, but there is still a lack of evidence-based support for the regulation of sex hormone levels. In recent years, new randomized clinical trials (RCTs) have been reported on the effect of combined therapy on regulating sex hormone levels. Objective We aimed to systematically evaluate the efficacy of Kuntai capsule combined with LE in the treatment of PCOS. Methods A search across the China Biomedical Literature Database (CBM), China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), Wanfang database, PubMed, Web of Science, The Cochrane Library, and Embase was conducted on Kuntai capsule combined with LE in the treatment of PCOS. The time of the self-built database was up to April 30, 2021. RCTs of LE in the control group and LE combined with Kuntai capsule in the experimental group were selected. RevMan5.3 software was used for data analysis. Results A total of 17 studies were gathered, which included 1,684 patients. The meta-analysis results showed that the total effective rate of the combined group was 93.36% and that of the LE group was 78.15%. The improvement in the ovulation rate, pregnancy rate, number of mature follicles, endometrial thickness, cervical mucus score, and serum follicle stimulating hormone (FSH), luteinizing hormone (LH), and prolactin (PRL) in the combined group was consistent with the results of a previous meta-analysis and was better than that in the LE group (p < 0.05). In addition, the combination group was better than the LE group in regulating the levels of estradiol (E2) and testosterone (T) (p < 0.05). There were no adverse drug reactions in the two groups during treatment. Conclusion As a type of pure traditional Chinese medicine preparation, Kuntai capsule combined with LE had a better effect than LE alone in the treatment of PCOS, with advantages mainly reflected in enhancing ovarian function and regulating the levels of sex hormones in vivo, among others, but the value of combined therapy still needs to be verified by more high-quality RCTs.